DEVELOPING DIGITAL BANKING PLATFORM STRATEGIES FOR FUTURE CHALLENGES USING SCENARIO PLANNING - I Gusti Agung Ayu Dianintha Andari; Santi Novani (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
The study explores strategies for digital banking platforms in Indonesia, emphasizing scenario planning to address future challenges. Indonesia’s digital banking sector, propelled by technological growth and changing consumer preferences, faces critical challenges such as regulatory fluctuations, intense competition, cybersecurity risks, and low financial literacy. Using Allo Bank as a case study, this research employs PESTLE and SWOT analyses, along with scenario planning, to evaluate strategic responses to key uncertainties in regulation, consumer behavior, and technology. The findings reveal that scenario-based planning enhances adaptability in digital banking, enabling Allo Bank to proactively navigate market complexities and leverage opportunities. Key recommendations include investment in regulatory compliance, technology for secure digital operations, and continuous innovation to maintain competitiveness in a volatile regulatory environment. This study underscores the importance of adaptive strategies for sustained growth in Indonesia’s dynamic digital banking ecosystem.